Sabías a lo que venías and The Tonight Show: Similarities and influences - Meliveo Nogués, Paula; Cristófol Rodríguez, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
After contextualizing Santiago Segura's figure as a scriptwriter in the Spanish precedents of his late show, its structure and contents have been studied. The methodology applied has been the case study and content analysis. Among other conclusions, it is established that the structure and fragmentation of contents narratively unified by the figure of the host, the program of La Sexta manifests common characteristics inherited from the American show The Tonight Show. Regarding other elements, it is observed that they undergo an adaptation subject to the journalistic trajectory of the director.